"Habitus" in soul care. Towards "spiritual fortigenetics" (parrhesia) in a pastoral anthropology - D. J. Louw (Acta Theologica)
It is argued that habitus plays a fundamental role in both a practical theological and pastoral-anthropological approach in order to focus on the “wholeness” of the human soul (soul as a qualitative and relational entity). It is hypothesized that a spiritual understanding of fortigenetics and the emphasis on a positive growth model can help pastoral theology to develop a theological theory for the empowerment of the being functions of human beings. In this regard, the theological notion of parrhesia can play a decisive role. The article proposes a paradigm shift from pathogenic thinking to growth thinking within the parameters of hope care.